Heart failure following blood cancer therapy in pediatric and adult populations. Issue 3 (12th October 2017) - Franzon, Julie; Berry, Narelle M.; Ullah, Shahid; Versace, Vincent L.; McCarthy, Alexandra L.; Atherton, John; Roder, David; Koczwara, Bogda; Coghlan, Douglas; Clark, Robyn A.
Abstract: Aim: The link between chemotherapy treatment and cardiotoxicity is well established, particularly for adults with blood cancers. However, it is less clear for children. This analysis aimed to compare the trajectory and mortality of children and adults who received chemotherapy for blood cancers and were subsequently hospitalized for heart failure. Methods: Linked data from the Queensland Cancer Registry, Death Registry and Hospital Administration records for initial chemotherapy and later heart failure were reviewed (1996–2009). Of all identified blood cancer patients ( N = 23 434), 8339 received chemotherapy, including 817 children (aged ≤18 years at time of cancer diagnosis) and 7522 adults. Time‐varying Cox proportional hazards regression models were used to compare the characteristics and survival between the two groups. Results: Of those who were subsequently hospitalized for heart failure, 70% of children and 46% of adults had the index admission within 12 months of their cancer diagnosis. Of these, 53% of the pediatric heart failure population and 71% of the adult heart failure population died within the study period. Following adjustment for age, sex and chemotherapy admissions, children with heart failure had an increased mortality risk compared to their non‐heart failure counterparts, a difference which was much greater than that between the adult groups. Conclusion: The impact of heart failure on children previously treated for blood cancer is more severe than for adults, with earlier morbidity and greater mortality. Improved strategies are needed for the prevention and management of cardiotoxicity in this population.